Elastica degeneration and intimal hyperplasia lead to Contegra® conduit failure. (6th July 2019) - Peivandi, Armin Darius; Seiler, Martina; Mueller, Klaus-Michael; Martens, Sven; Malec, Edward; Asfour, Boulos; Lueck, Sabrina
Abstract: OBJECTIVES: Currently, Contegra ® grafts (processed bovine jugular vein conduits) are widely used for reconstructive surgery of the right ventricular outflow tract in patients with congenital heart disease (CHD). We analysed explanted Contegra conduits from 2 institutions histologically to get a possible hint at the underlying pathomechanisms of degenerative alterations and to find histological correlations of graft failure. Additionally, we compared the explants with a non-implanted processed graft and a native jugular vein obtained from a young bull. METHODS: The explanted Contegra grafts were gathered during reoperations of 13 patients (male: n = 9, 69.2%; female: n = 4, 30.8%). After standardized histological preparation, samples were stained with dyes haematoxylin and eosin and Elastica van Gieson. Additionally, X-ray pictures revealed the extent of calcification and chelaplex (III)-descaling agent was used to decalcify selected explants. RESULTS: Processing of the native jugular vein leads to tissue loosening and a loss of elastic fibres. For graft failure after implantation, 2 pathomechanisms were identified: original graft alteration as well as intimal hyperplasia. Elastica degeneration and rearrangement with interfibrillary matrix structures were the main developments observed within the graft itself. Intimal hyperplasia was characterized by fibrous tissue apposition, calcification and heterotopic ossification. CONCLUSIONS: Regression of the elastic fibre network leads to rigidification of the conduit. In Contegra grafts, atherosclerosis-like changes can be considered the leading cause of graft stenosis and insufficiency. We conclude that both observed mechanisms lead to early reoperation in CHD patients.